Feedforward resonance control for the European X-ray free electron laser high duty cycle upgrade - Bellandi, Andrea; Branlard, Julien; Schlarb, Holger; Schmidt, Christian (Frontiers in Physics, 2023)
The High Duty Cycle (HDC) upgrade is a proposed improvement to the existing European X-ray Free Electron Laser (EuXFEL) to extend the pulsed RF duty factor from the actual value of around 1% to more than 5% up to Continuous Wave (CW). To implement this upgrade, the loaded quality factor (QL) of the superconducting cavities will increase by more than one order of magnitude. This will result in shrinking the cavity bandwidth to values as low as a few Hertz. Since the Lorentz Force Detuning (LFD) experienced during the accelerating field buildup is of hundreds of Hertz, the Low-Level RF (LLRF) system has to accurately track and control the cavity resonance frequency to obtain the desired accelerating gradient. Moreover, ponderomotive instabilities have to be suppressed to achieve stability during beam acceleration. Since LFD is a repetitive disturbance in cavity frequency, the correction to its effects can be implemented as a feedforward compensation on the piezoelectric tuners of the cavity. Initial results on the simulation of feedforward resonance control in the HDC regime are discussed in this proceeding.